Pengaruh Performance Expectancy, Effort Expectancy,Facilitating Conditions, Social Influence, Attitude Towards Use, Pemakaian Aplikasi Zakat - Bunga Tasya, Nadezhda; Sumardi, Arwini (Fakultas Ekonomi Universitas Gresik, 2023)
The purpose of this study was to examine the factors that influence adolescents' intentions to use social networking media to understand online zakat campaigns that use creative animation. Data was obtained by distributing questionnaires online to users of the zakat application